2007
DOI: 10.1017/s1740925x07000580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating neuronal and glial growth on electrospun polarized matrices: bridging the gap in percussive spinal cord injuries

Abstract: One of the many obstacles to spinal cord repair following trauma is the formation of a cyst that impedes axonal regeneration. Accordingly, we examined the potential use of electrospinning to engineer an implantable polarized matrix for axonal guidance. Polydioxanone, a resorbable material, was electrospun to fabricate matrices possessing either aligned or randomly oriented fibers. To assess the extent to which fiber alignment influences directional neuritic outgrowth, rat dorsal root ganglia (DRGs) were cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 25 publications
(26 reference statements)
3
71
0
Order By: Relevance
“…Since this work and other reports [13][14][15][16]28,37 demonstrate aligned astrocytes are conducive for enhanced and directed neuronal growth, we postulated that this could provide a novel basis for an implantable device to bridge spinal cord injuries. Previous studies have shown how cells in tethered aligned collagen gels can be delivered to peripheral nerve injury sites, 29 but the requirement for external tethering and overall fragility of such devices makes this unsuitable for clinical CNS repair.…”
Section: Aligned Astrocyte Construct For Implantation Supports Alignementioning
confidence: 64%
“…Since this work and other reports [13][14][15][16]28,37 demonstrate aligned astrocytes are conducive for enhanced and directed neuronal growth, we postulated that this could provide a novel basis for an implantable device to bridge spinal cord injuries. Previous studies have shown how cells in tethered aligned collagen gels can be delivered to peripheral nerve injury sites, 29 but the requirement for external tethering and overall fragility of such devices makes this unsuitable for clinical CNS repair.…”
Section: Aligned Astrocyte Construct For Implantation Supports Alignementioning
confidence: 64%
“…The number of studies investigating the influence of surface features on glial cells is increasing, yet focused on astrocytes, mainly due to astrocytes' key role in the formation of the glial scar in response to an injury to the CNS [12]. Astrocytes have been found to orientate their filamentous structure according to the features of the surface [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The neurites grew in a radial manner on the aligned nanofibers. Those that grew in the direction of the fibers had a faster growth rate than the others indicating that the aligned nanofibrous scaffolds served in guiding neurite orientation and cell alignment (Chow et al, 2007).…”
Section: Neural Tissue Regenerationmentioning
confidence: 99%